2016
DOI: 10.2337/db16-0773
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Cyclooxygenase-2 Protects Against Development of Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is characterized by increased macrophage infiltration, and proinflammatory M1 macrophages contribute to development of DN. Previous studies by us and others have reported that macrophage cyclooxygenase-2 (COX-2) plays a role in polarization and maintenance of a macrophage tissue-reparative M2 phenotype. We examined the effects of macrophage COX-2 on development of DN in type 1 diabetes. Cultured macrophages with COX-2 deletion exhibited an M1 phenotype, as demonstrated by higher induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 45 publications
(50 reference statements)
1
58
0
Order By: Relevance
“…Our previous studies indicated that GPR40 is expressed in the mouse kidney, with the highest expression in the cortex and outer stripe of the outer medulla, and is most highly expressed in the epithelia (10). In contrast, GPR84 is abundantly found in monocytes/macrophages, granulocytes, and neutrophils, and it has been reported to mediate inflammatory cell activation (5,15,23). It is notable that there was markedly decreased inflammatory infiltrate following PBI-4050 treatment in renal tissue of both models of kidney injury.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our previous studies indicated that GPR40 is expressed in the mouse kidney, with the highest expression in the cortex and outer stripe of the outer medulla, and is most highly expressed in the epithelia (10). In contrast, GPR84 is abundantly found in monocytes/macrophages, granulocytes, and neutrophils, and it has been reported to mediate inflammatory cell activation (5,15,23). It is notable that there was markedly decreased inflammatory infiltrate following PBI-4050 treatment in renal tissue of both models of kidney injury.…”
Section: Discussionmentioning
confidence: 91%
“…In our initial studies, we treated mice with either vehicle or PBI-4050 (100 mg/kg) by daily gavage from 8-20 weeks of age. eNOS -/db/ db mice are moderately hypertensive (14,15), and PBI-4050 had no effect on blood pressure (Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/ jci.insight.120365DS1). In addition, there was no effect on body weight with PBI-4050 administration compared with vehicle-treated mice (Supplemental Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The relevance of M1 to the development of DN has been shown using mice with Mϕ cyclooxygenase-2 (Cox-2) deletion. These mice demonstrate increased M1 polarization, which is associated with increased renal injury [69]. Although other authors found that Mϕ in the kidneys of streptozotocin-induced DN rat are characterized by an elevated expression of galectin-3 and TGF-β, suggesting an M2 dominance [59].…”
Section: Macrophage Phenotype and Diabetic Nephropathymentioning
confidence: 91%
“…For example, macrophages consist of two subtypes, the pro-inflammatory M1 type and an anti-inflammatory M2 type. It has been reported that M1 type macrophages promote renal fibrosis requiring the presence of COX-2 [37]. Our research team sorted out Ly6C-macrophages in mice kidney at 5 days after IR operation and injected them under the renal capsule of mice with immune deficiency, finding that the original normal kidney showed damage and intrarenal fibrosis 5 days later, suggesting that Ly6C-macrophages directly damaged kidney and induced subsequent fibrosis [38].…”
Section: Lvs Serve As a Bridge Between Innate And Adaptive Immunitymentioning
confidence: 91%